TNF-α as a Therapeutic Target in Acute Pancreatitis — Lessons from Experimental Models - Giuseppe Malleo; Emanuela Mazzon; Ajith K. Siriwardena; Salvatore Cuzzocrea (The Scientific World Journal)
A considerable body of experimental evidence suggests that tumor necrosis factor (TNF)-α plays a major role in several aspects of inflammation and shock. In particular, it is pivotal in many detrimental effects of acute pancreatitis, and it represents a major determinant of the systemic progression and end-organ damage (such as acute lung injury and liver failure) of this pathologic condition. Given the importance of TNF-α in the pathogenesis of acute pancreatitis, investigators have regarded blocking the action of this mediator as an attractive treatment option. Different specific and nonspecific inhibitors have been developed with promising results in animal models, but, on the other hand, no clinical trials have been designed so far. Difficulties in clinical applications may be multifactorial; experimental models are not fully reliable and reproduce at least some aspects of human disease, timing of intervention should be related to changes in TNF-α serum levels, and inclusion criteria should be accurately selected to better define the population most likely to benefit.